Estado e terceiro setor na prestação de serviços públicos: o programa Nacional de DST e Aids: 1994-2005 - Campos, Luiz Claudio Marques (2005)
This dissertation aims at analyzing the reasons why State contracts civil society organizations to deliver public services. In order to do that, we take as example the national HIV/Aids public policy, conducted by the National Aids Program of the Ministry of Health, which is a well known reference in making partnerships with these organizations. The analysis is developed trying to answer 3 questions: the reasons of the partnership, the areas or sorts of services where this partnership happens and what are the contract mechanisms. The dissertation shows the construction of a partnership policy, starting from the difficulties of State in providing many services in HIV/Aids policy, which were already well delivered by non-governmental organizations. It is established a task-division, in which NGOs will deliver many activities on prevention, care and human rights, especially with to so-called most vulnerable population groups. After few years of centralization in federal government, this policy is being decentralized, stronger involving local levels of government. Inside this process, there is a conflict, not solved yet, regarding the “ownership” of these services: whether they will be absorbed by State or will keep being delivered by NGOs. Even though, decentralization policy stated a way to guarantee a minimum percentage of funds in each state of federation, which shall be used in NGOs projects and means an institutionalization of this partnership policy.